Functional and aesthetic approach to design of bird feeders; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Kukhta A. E. Atrem Evgenjevich (Design and artistic aspects of engineering, 2015)
Title screen